PENGARUH KOMITMEN ORGANISASI, PELATIHAN DAN MOTIVASI TERHADAP KINERJA PELATIH GURAKLIH/SAKSI TINGKAT NASIONAL DI BADAN SAKSI PEMILU NASIONAL PARTAI DEMOKRASI INDONESIA PERJUANGAN - Yulianti .; Chandra Suwondo; Andy Yusfany (LPPM STIE PERTIBA Pangkalpinang, 2018)
This study aims to analyze the effect of organizational commitment, training, and motivation on the performance of guraklih/national level witnesses in the national election witnesses' bodies of the Indonesian Democratic party struggle either simultaneously or partially. The sample size is 52 from the number of 60 national witness trainers in the national election witnesses of the PDIP party. The research instrument used questionnaires, arranged on a scale of 1-5, score 1 for very poor responses and a score of 5 for excellent responses. Analysis method using path analysis (Path analysis). Hypothesis testing using an F test (simultaneous) and t-test (partial). The result of this research concludes that there is the significant influence of organizational commitment, training and motivation variable to the performance of the witness trainer either simultaneously or partially, seen from the coefficient of determination equal to 84 percent.